“A Free, United South Africa Under the Union Jack”: F.S. Malan, South Africanism and the British Empire, 1895–1924 (Historia, 2021)
EnglishDuring his turbulent career as newspaper editor and politician, Francois Stephanus Malan elicited strong and conflicting reactions. In the late nineteenth century, English-speaking South Africans and imperial officials regarded him as an insidious republican and a bitter enemy of Britain. During the Anglo-Boer War, they clamoured for his imprisonment. After Union in1910, however, he was increasingly seen as a defender of the British Empire and he rose to the rank of privy councillor. For many Afrikaners he was a hero who became a renegade and a puppet of British imperialism. Despite the conflicting views, Malan’s political vision remained remarkably unchanged over the years. He campaigned for a united South Africa free from internal British control, but an integral part of the Empire, which he regarded as essential to secure a stable, prosperous society in which Afrikaners and English-speakers could overcome their enmity and become one nation. Malan played a leading role in the unification of South Africa, as well as the Union’s growing autonomy within the Empire, but in the process he sacrificed his political career. Trapped between a retreating British imperialism and an advancing Afrikaner nationalism, Malan’s public career was shattered in the general election of 1924.  Afrikaans“ŉ Vry, Verenigde Suid-Afrika onder die Union Jack”: F.S. Malan, Suid-Afrikanisme en die Britse Ryk, 1895-1924 Tydens sy stormagtige loopbaan as koerantredakteur en politikus, het Francois Stephanus Malan sterk en botsende reaksies uitgelok. In die laat negentiende eeu, het Engelssprekendes en imperiale amptenare hom as ŉ verraderlike republikein en bittere vyand van Brittanje veroordeel. Gedurende die Anglo-Boereoorlog is op sy arrestasie aangedring. Na Uniewording in 1910 is hy egter toenemend as ŉ beskermer van die Britse Ryk gesien en tot die Geheime Raad bevorder. Vir talle Afrikaners was hy ŉ held wat ŉ afvallige en ŉ handlanger van Britse imperialisme geword het. Ondanks hierdie uiteenlopende standpunte, het Malan se visie oor die jare merkwaardig onveranderd gebly. Hy het hom vir ŉ verenigde Suid-Afrika, vry van interne Britse beheer, maar steeds as ŉ integrale deel van die Ryk, beywer. Hy was van mening dat die imperiale band noodsaaklik was om ŉ stabiele, florerende gemeenskap te skep waarin Afrikaans- en Engelssprekendes hulle vyandigheid kon oorkom om een nasie te vorm. Malan het ŉ belangrike rol gespeel in die unifikasie van Suid-Afrika, sowel as die Unie se toenemende selfbestuur binne die Ryk, maar het in die proses sy politieke loopbaan opgeoffer. Vasgevang tussen die terugwykende Britse imperialisme en ŉ voortstuwende Afrikanernasionalisme, is sy openbare loopbaan in die algemene verkiesing van 1924 verpletter.
Keywords: Afrikaner Bond; Afrikaner nationalism; autonomy; British Empire; Commonwealth; F.S. Malan; National Party; Ons Land; South African Party; South Africanism; unification; Afrikanernasionalisme; Britse Ryk; Nasionale Party; selfbestuur; Statebond; Suid-Afrikaanse Party; Suid-Afrikanisme; unifikasie